2021
DOI: 10.3389/fonc.2021.614458
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide Combined With Doxorubicin Induced p53-Driven Cell Cycle Arrest and Cell Apoptosis Reverse Multidrug Resistance of Breast Cancer

Abstract: The multidrug-resistant (MDR) phenotype is usually accompanied by an abnormal expression of histone deacetylase (HDAC). Given that HDAC is vital in chromatin remodeling and epigenetics, inhibiting the role of HDAC has become an important approach for tumor treatment. However, the effect of HDAC inhibitors on MDR breast cancer has not been elucidated. This study aim to demonstrate the potential of chidamide (CHI) combined with the chemotherapy drug doxorubicin (DOX) to overcome chemotherapeutic resistance of br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…Thus, research on therapeutic agents with multiple targets will become very attractive, for multiple oncogenic signaling pathways can be simultaneously targeted increasing the likelihood of overcoming MDR in difficult-to-treat cancer. A recent study demonstrated that chidamide combined with doxorubicin (DOX) could suppress MDR breast cancer cells through synergistically modulation of multiple signaling pathways [31]. In the current study, chidamide was shown to possess an antitumor effect in TSCC in vitro through multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, research on therapeutic agents with multiple targets will become very attractive, for multiple oncogenic signaling pathways can be simultaneously targeted increasing the likelihood of overcoming MDR in difficult-to-treat cancer. A recent study demonstrated that chidamide combined with doxorubicin (DOX) could suppress MDR breast cancer cells through synergistically modulation of multiple signaling pathways [31]. In the current study, chidamide was shown to possess an antitumor effect in TSCC in vitro through multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, emerging data from in vitro studies indicate that HDAC inhibitors, such as chidamide, may have improved activity when used in combination therapy (52)(53)(54). To this end, several recent studies have provided a strong preclinical rationale for combination with chemotherapy, immunotherapy, or molecular targeted therapy, paving the way for possible studies in selected populations (53)(54)(55). In our previous work, we revealed that ABT-199 (25) or MLL-menin inhibitor (56) has a synergistic inhibitory effect on acute myeloid leukemia cells when combined with chidamide.…”
Section: Discussionmentioning
confidence: 99%
“…As the activity of chidamide, as monotherapy at the doses tested in this study was modest, understanding potential biomarkers that are predictive of response is very important for the design of future clinical trials ( 51 ). In addition, emerging data from in vitro studies indicate that HDAC inhibitors, such as chidamide, may have improved activity when used in combination therapy ( 52 – 54 ). To this end, several recent studies have provided a strong preclinical rationale for combination with chemotherapy, immunotherapy, or molecular targeted therapy, paving the way for possible studies in selected populations ( 53 – 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The acetylation modi cation of p53 is completed by the CBP/p300 of HATs or the TIP60/ hMOF of MYST family, and the deacetylation modi cation is controlled by HDAC [31]. Studies have con rmed that HDAC1, HDAC2, and HDAC3 are involved in the deacetylation process of p53 [32][33][34]. The destruction of deacetylation at different sites of p53 by inhibiting HDAC may affect the binding activity of sequence-speci c DNA, thereby activating target genes or altering nuclear export, coactivator recruitment or p53 stability.…”
Section: Discussionmentioning
confidence: 99%